A Fit-For-Purpose Approach to Land Administration in Africa - Musinguzi, Moses; Enemark, Stig (International Journal of Technoscience and Development, 2019)
Land is the most important resource for many developing countries in Africa to achieve the sustainable development goals. Yet many African countries are faced with various problems often causing land conflicts, reducing investments and economic development, and preventing countries reaching their true potential. Africa and other developing countries will not efficiently utilize their land resources as a means to overcome these challenges, unless they drop the approaches to security of tenure, many of which, were introduced during colonial times, but have not helped in securing land tenure rights for a significant proportion of their populations, in a non-discriminatory manner, that leaves no body behind. In this paper, we describe the key principles for building flexible, universal and sustainable Fit for Purpose (FFP) land administration (LA) systems in African countries, as a better alternative to conventional approaches that focus on unrealistic accuracy standards and complex legal procedures. The discussion informed by a review of literature on Fit for Purpose Land Administration, the sustainable development goals, and the authors experience on land administration systems in Africa and globally. Furthermore, two experiences from Rwanda and Uganda are introduced to demonstrate that building FFP land administration systems is a viable solution to solving the global security of tenure divide.We conclude that implementation of Fit for Purpose Land Administration approach requires political support at national and local level, to facilitate the change process, and in embedding FFP LA provisions into national and local laws. Likewise, effective capacity building is fundamental to the success of such programs. Professionals and the general society must understand that these simpler, less expensive and participatory methods are just as effective and secure as conventional land surveying methodologies and judicial recordation procedures. Finally, involvement of development partners such as Global Land Tool Network (GLTN), The World Bank, United Nations Global Geospatial Information Management (UNGGIM), The United Nations Human Settlements Programme (UN- HABITAT) and Food and Agriculture Organization of the United Nations (UN FAO) is key in ensuring that the land administration projects technically and financially supported are designed around FFP concepts.
supporting the 2030 Global Agenda